Characterization of a site-specific restriction endonuclease from Streptomyces aureofaciens. - Timko, J (1981)
A new type II sequence-specific restriction endonuclease, SauI, was isolated from Streptomyces aureofaciens IKA18/4. The purified enzyme was free of contaminating exonuclease and phosphatase activities. SauI cleaved lambda DNA at two sites, but did not cleave pBR322, simian virus 40, or phi X174 DNA. SauI recognized the septanucleotide sequence 5'-CCTNAGG-3' and cleaved at the position indicated by the arrow, producing a trinucleotide 5'-terminal extension.